Critical success and failure factors in SMEs - the retailing sector / Sofiah Abd Rahman ... [et al.] - Abd Rahman, Sofiah; Mohd Roslin, Rosmimah; Salleh, Zarina; Mohd Yusof, Yuslina Liza (Research Management Institute (RMI), 2008)
Recently, SMIDEC has extended its instrument, acronym SCORE, to measure the 'state of health' of SMEs in the distributive sector. Through this tool, SMEs are rated against six dimensions of capabilities: management, financial, compliance, stock management, marketing, and operations management. The outcome provides an input in identifying the appropriate incentive/assistance and in linking potential SMEs to suitable global partners. This study primarily sets out to assess and enhance this instrument and to compare the success/failure factors of SMEs against SME categorization and ethnicity. An exploratory study by means of focus groups was first undertaken and as a result, non-compliance was included in this study. 'Innovation', another critical dimension to business success, was also incorporated into the framework. Using a stratified area sampling method, 503 SMEs were administered the survey instrument. Data analyses uncovered several key findings. Bumiputera SMEs had better educational background than their non-Bumiputeras counterparts, they claimed to work longer hours, and they rated themselves as having higher positive entrepreneurial traits but their returns (both on revenue and profits) were lower, indicating inefficiency and ineffectiveness in running the retail businesses. All capabilities contributed to the retail SMEs success led by innovation (fi = 0.362), marketing (fi = 0.310), and operations management (fi = 0.310), while non-compliance, proved to be detrimental (fi = -0.195). This study, thus, points out the need to include 'innovation' capability in measuring the 'state of health' of SMEs in the distributive sector and must be included in SCORE.